Coupled pyroelectric-photovoltaic effect in 2D ferroelectric α-In 2 Se 3 - Michael Uzhansky; Abhishek Rakshit; Yoav Kalcheim; Elad Koren (npj 2D Materials and Applications)
Abstract Pyroelectric and photovoltaic effects are vital in cutting-edge broadband sensors and solar energy harvesting. Recent advances revealed great potential of the bulk photovoltaic effect in two-dimensional (2D) materials to surpass the Shockley-Queiseer limit. Moreover, the atomic thickness, high thermal conductivity and room-temperature ferroelectricity endow 2D ferroelectrics with a superior pyroelectric response. Herein, we combined direct pyroelectric-photovoltaic measurements in 2D α-In2Se3. The results reveal a gigantic pyroelectric coefficient of ∼30.7 mC/m2K and a figure of merit of ∼135.9 m2/C. Moreover, a coupled pyroelectric-photovoltaic effect was demonstrated, where the pyroelectric current follows the temperature derivative, while the short-circuit current follows temperature. Finally, we utilized the intercoupled ferroelectricity of In2Se3 to realize a non-volatile, self-powered photovoltaic memory operation, demonstrating stable short-circuit current switching with 103 ON-OFF ratio. The coupled pyroelectric-photovoltaic effect, along with reconfigurable photocurrent, pave the way for a novel integrated thermal and optical response, in-memory logic and energy harvesting.